2007
DOI: 10.1016/j.freeradbiomed.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α activation by a redox-sensitive pathway mediates cyanide-induced BNIP3 upregulation and mitochondrial-dependent cell death

Abstract: Cyanide produces degeneration of the nervous system in which different modes of cell death are activated in the vulnerable brain areas. In brain, the mechanism underlying the cell death is not clear. In this study, an immortalized dopaminergic cell line was used to characterize the cell death signaling cascade activated by cyanide. Cyanide-treated cells exhibited a time-and concentration-dependent apoptosis that was caspase-independent. Cyanide induced a rapid surge of intracellular reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
3
39
0
1
Order By: Relevance
“…An et al (2) have previously shown that whereas U0126, a specific MEK inhibitor, completely abolished BNIP3 expression and the stimulation of promoter activity by NO and Ras in macrophages, the specific inhibitor of p38 MAPK SB 203580 had no effect. In contrast, the same selective p38 MAPK inhibitor blocked the activation of both the p38 MAPK and the HRE promoter necessary for nuclear accumulation of HIF-1␣ and BNIP3 gene transcription following exposure to cyanide in an immortalized dopaminergic cell line (56). Our results showing that the p38 MAPK inhibitor SB 203580 blocked the hypoxia-mediated upregulation of BNIP3 suggest that activation of the p38 MAPK pathway, but not the JNK pathway, is necessary for BNIP3 protein upregulation under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 58%
“…An et al (2) have previously shown that whereas U0126, a specific MEK inhibitor, completely abolished BNIP3 expression and the stimulation of promoter activity by NO and Ras in macrophages, the specific inhibitor of p38 MAPK SB 203580 had no effect. In contrast, the same selective p38 MAPK inhibitor blocked the activation of both the p38 MAPK and the HRE promoter necessary for nuclear accumulation of HIF-1␣ and BNIP3 gene transcription following exposure to cyanide in an immortalized dopaminergic cell line (56). Our results showing that the p38 MAPK inhibitor SB 203580 blocked the hypoxia-mediated upregulation of BNIP3 suggest that activation of the p38 MAPK pathway, but not the JNK pathway, is necessary for BNIP3 protein upregulation under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 58%
“…However, treatment of the tissues with NAC fully reversed the E GSH to normality, but normalization of the redox status did not modify their neurosecretory power. These last observations coupled to the well known ability of NAC to buffer the increased production of ROS induced by complex III and IV inhibitors in many cell systems (Watabe and Nakaki, 2007;Stöckl et al, 2006;Suzuki et al, 1998;Satpute et al, 2008;Zhang et al, 2007), would indicate that there is not any relationship between ROS levels and chemoreceptor cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…The JC-1-stained cells referred to above were processed to measure the green/red fluorescent intensity ratio as described previously (55). Briefly, at the end of the JC-1 experiment as mentioned above, cells were seeded in a 96-well plate (flat, clear bottom, Corning) at a density of 50,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%